Implementation of Integrated Administrative Service Policy "Meladen Dang Asak'ng" - Andre Fernanda; Ida Bagus Made Agung Dwijatenaya; Agustinus Djiu (Journal Research of Social Science, Economics, and Management, 2022)
Changes in government that were previously centralized to become decentralized certainly have an impact on the concept of public service delivery. Problems in the District Integrated Administration Service located in the sub-district under the auspices of the district are certainly different from handling problems in the city. One of the problems that often lands on the services implemented by the Linggang Bigung District office, West Kutai Regency, lies in internet network problems, it is not uncommon for services that are being carried out to be forced to stop because of problematic internet networks, so that it often causes pending files. This study aims to describe and analyze the sub-district integrated administrative services in Linggang Bigung District, West Kutai Regency, describe and analyze the implementation of the sub-district integrated administrative service policy in Linggang Bigung District, West Kutai Regency, describe and analyze the supporting factors and obstacles to the successful implementation of service policies. integrated administration of sub-districts in Linggang Bigung District, West Kutai Regency. This study uses a qualitative approach, with a descriptive type of research, while the research location is in the Linggang Bigung District office, West Kutai Regency, the data collection techniques used are interview, observation, and documentation techniques. While the research instruments are the researchers themselves, interview guides, and communication and documentation tools. The data analysis of this research used an interactive model, namely data reduction, data presentation, and conclusion data verification.